Validation of the Slovenian version of the low anterior resection syndrome score for rectal cancer patients after surgery - Grosek Jan; Košir Jurij Aleš; Novak Jerica; Omejc Mirko; Tomažič Aleš; Norčič Gregor (Sciendo, 2019)
The purpose of this study was to translate the low anterior resection syndrome (LARS) score into Slovenian and to test its validity on Slovenian patients who underwent low anterior rectal resection.